1930
DOI: 10.1037/h0071535
|View full text |Cite
|
Sign up to set email alerts
|

Relation of bodily tension to electrical resistance.

Abstract: The general problem of this experiment was to compare the electrical resistance of the subject during relaxation with his resistance during bodily tension. The electrical resistance of the human body has been studied by many investigators under various conditions. It has been studied with reference to the activity of the sweat glands by Darrow (i), Einthoven and Roos (3), Georgi (4), Markbreiter (6), Waller (11), and Wells and Forbes ( 14). It has been studied with reference to circulation by Jung (5), Sidis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1936
1936
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…showed a slow decrease in conductance (or increase in resistance). They state that this decrease was also noted by White (34). It thus appears that adaptation may occur even during a period of relatively uncontrolled stimulation, on any given day and, as we have pointed out above, from day to day (see Table II).…”
Section: Day-to-day Adaptationsupporting
confidence: 65%
“…showed a slow decrease in conductance (or increase in resistance). They state that this decrease was also noted by White (34). It thus appears that adaptation may occur even during a period of relatively uncontrolled stimulation, on any given day and, as we have pointed out above, from day to day (see Table II).…”
Section: Day-to-day Adaptationsupporting
confidence: 65%
“…This result is to be expected because of the degree of tension created. These data confirm those of White (15) who observed that resistance is decreased with tension. With the exception of one movement of one O (crossing of knee) all movements caused a decrease of resistance.…”
supporting
confidence: 92%
“…Usually, too, such a movement resulted in a curve of irregular shape, quite different from the characteristic curve of the psychogalvanic reflex. White (15) compared electrical resistance during relaxation with resistance during bodily tension. He used a dynamometer to produce one type of tension and voluntary bodily tension for another type.…”
mentioning
confidence: 99%
“…Palmar skin conductance, for example, has been found to vary directly with variations in tension of the muscles (6,13,9). Muscular tension would also correlate, no doubt, with insensible weight loss or other measures of metabolic activity.…”
Section: T Ime Arrangement Of Tasksmentioning
confidence: 99%